Genome assembly of the Baikal seal Pusa sibirica ... - Nebenführ, Marcel; Arnason, Ulfur; Janke, Axel (GigaScience Database, 2024)
Pusa sibirica , the smallest true seal, is a freshwater seal that is endemic to Lake Baikal where it became landlocked some million years ago. It is a rather abundant species of least concern, with an estimated population between 80,000 to 100,000 animals, despite the limited habitat. The precise origin of the species remains ambiguous; however, the prevailing theory posits that it descends from the ringed seal, Phoca hispida , and indicates that the species may have experienced geographical isolation for approximately 500,000 years. Until recently, research on its genetic diversity has only been done on mitochondrial genes, restriction fragment analyses, and microsatellites, before its reference genome has been published. Here we present a publicly available genome assembly of the Baikal seal Pusa sibirica , with 75 Gb (~32-fold coverage) of sequence data. The complete assembly spans 2.3 Gb, with contig N50 of 15 kb and scaffold N50 of 173 Mb. The BUSCO analysis indicates a completeness of 89.5%. ...